"A Most Important Cadre": The Infiltration of the Communist Party of Australia during the Early Cold War. (November 2018) - Deery, Phillip
Abstract : The Australian labour movement has a long history of its ranks being infiltrated by the security services. Rarely, however, are we permitted inside undercover operations. To protect undercover agents, files remain classified and agents' identities and activities are shrouded in secrecy. This article uses, for the first time, a trove of declassified Australian Security Intelligence Organisation files of one of its agents, Anne Neill, whose target was the Communist Party of Australia. It examines her relationship with the CPA, which she successfully penetrated, and ASIO, to which she reported. A primary purpose of this penetration was to report on subversive activity and, over eight years, from 1950 to 1958, Neill submitted hundreds of highly detailed reports. The paper also examines the agent's life after her employment with ASIO ceased, especially her embrace of far right-wing politics and the League of Rights.